Adherence to taking medicines as a basis for prevention of cardiovascular diseases - D. A. Napalkov; A. A. Sokolova (Медицинский совет, 2019)
The article discusses approaches to improving adherence to treatment with antihypertensive drugs and statins based on domestic and foreign experience, in particular, with the help of approaches proposed in the recommendations of the European Society of Cardiologists on Diagnostics and Treatment of Arterial Hypertension (ESC), updated in 2018. It is proposed to consider several levels to improve adherence: the level of the physician, the patient’s level, the level of prescription and the level of the healthcare system. The implementation of the principle of reducing the number of pills for the treatment of arterial hypertension can be achieved through the increased use of fixed combinations, such as lysinopril and prolonged action indapamide or lysinopril and amlodipine at the 1st stage of treatment selection. In the 2nd stage, a triple fixed combination of lysinopril, amlodipine and prolonged action indapamide can be used, thus maintaining the continuity of the therapy initiated. In patients with concomitant dyslipidemia, the authors suggest a fixed combination of lysinopril, amlodipine and rosuvastatin, which also improves adherence to statin therapy.